Qualidade e metabolismo antioxidante durante a maturação e inovação na conservação pós-colheita de cultivares de abacaxi - Nascimento, Ricardo de Sousa (2019)
Brazil is a traditional pineapple producer, which is widely consumed due to its pleasant aroma and flavor, originating from a complex mixture of substances. The main cultivar is Pérola, which supplies the domestic market, but is susceptible to fusariosis, an important pineapple disease. However, in order to expand the offer in the markets, new cultivars have been introduced, such as Vitória, which is resistant to fusariosis, of which there is no information available about changes in antioxidant metabolism during maturation. With regard to the 'Pérola' pineapple, its high perishability is aggravated due to long distance transport and deficiencies in the production chains, thus requiring innovative strategies for postharvest conservation. The use of natural deep eutectic solvents (NADES) associated with the dispersion of cassava starch can be an efficient alternative for postharvest conservation of 'Pérola' pineapple. Therefore, the objectives of this work, for the Experiment I, was to evaluate the quality and antioxidant metabolism during the maturation of 'Vitória' pineapple and for the Experiment II, to use innovative strategies for postharvest conservation of 'Pérola' pineapple, by using of biodegradable coatings of cassava starch associated with NADES. The experimental designs were completely randomized. For the experiment I, 'Vitória' pineapple was studied in 6 maturity stages, totally green (TV), green (V), beginning of pigmentation (IP), orange green (VA), partially orange (PA) and totally orange (TA), in four repetitions. In ‘Vitória’ pineapple, the levels of SS, AT and the SS/AT ratio, β carotene, yellow flavonoids, total extractable polyphenols, and antioxidant activity increase as maturation advanced, especially in the PA stage. Pineapples from the PA maturity stage showed lower levels of H2O2 and higher activities of SOD and APX. Together, 'Vitória' pineapple presents the highest functional potential at the PA stage. In the experiment II, 'Pérola' pineapples harvested at commercial maturity were sanitized and coated with 2.5% cassava starch + NADES 0.75% (NADES + F); 2.5% starch + 0.75% Glycerol (F + G); 2.5% starch + 0.375% Glycerol + 0.375% NADES (F + G + NADES) and the control (without coating), in four repetitions of two pineapple, and stored at room condition (24 ± 3 °C and 74 ± 3 % RH) for 20 days. In pineapples covered with NADES + F, the respiratory rate was reduced, the loss of mass was minimized, the levels of ascorbic acid and higher antioxidant activity were maintained, without compromising the appearance’s acceptance of fruits, giving greater sensory acceptance. Together, coating with NADES + F provided the maintenance of quality and greater purchase intention of 'Pérola' pineapple during 20 days of storage at room conditions, featuring an efficient innovation in pineapple postharvest conservation.